Quantifying beliefs regarding telehealth: Development of the Whole Systems Demonstrator Service User Technology Acceptability Questionnaire. (May 2017) - Hirani, Shashivadan P; Rixon, Lorna; Beynon, Michelle; Cartwright, Martin; Cleanthous, Sophie; Selva, Abi; Sanders, Caroline; Newman, Stanton P
Introduction: Telehealth (TH) is a potential solution to the increased incidence of chronic illness in an ageing population. The extent to which older people and users with chronic conditions accept and adhere to using assistive technologies is a potential barrier to mainstreaming the service. This study reports the development and validation of the Whole Systems Demonstrator (WSD) Service User Technology Acceptability Questionnaire (SUTAQ). Methods: Questionnaires measuring the acceptability of TH, quality of life, well-being and psychological processes were completed by 478 users of TH. The 22 acceptability items were subject to principal components analysis (PCA) to determine sub-scales. Scale scores, relationships between scales and other patient-reported outcome measures (PROMs), and group differences on scales were utilised to check the reliability and validity of the measure. Results: PCAs of SUTAQ items produced six TH acceptability scales: enhanced care, increased accessibility, privacy and discomfort, care personnel concerns, kit as substitution and satisfaction. Significant correlations within these beliefs and between these scales and additional PROMs were coherent, and the SUTAQ sub-scales were able to predict those more likely to refuse TH. Discussion: The SUTAQ is an instrument that can be used to measure user beliefs about the acceptability of TH, and has the ability to discriminate between groups and predict individual differences in beliefs and behaviour. Measuring acceptability beliefs of TH users can provide valuable information to direct and target provision of services to increase uptake and maintain use of TH.